Study on Larsen Steel Sheet Pile as the Deep Base Pit Support. Issue 1 (June 2020) - Yang, Yang; Liu, Wanfeng; Hu, Aiping; Yang, Zhaoqian; Shen, Dilun
Abstract: The steel sheet pile, a material featuring good quality, easy construction, high durability and strong interchangeability, has few restrictions for projects, and is therefore widely used as the deep base pit support. However, the complexity and specificity of base pit supporting demands an appropriate method to install it, which is the prerequisite of project safety. To ensure the safety, the paper studied the deformation by force and stability of Larsen steel sheet pile. It found that both indicators meet the requirements. Larsen steel sheet pile can provide effective protection for the base pit with decent performance. Therefore, Larsen steel sheet pile should be advocated in projects alike.